Discovering the qualities of Ferringhi Night Market as an urban cultural space - Mohamad Kamarudin, Amirah; Abdul Wahab, Nur Amirah; Zakariya, Khalilah (2015)
Street market in urban centres has become a part of the major commercial place for locals and tourists. In most revitalization projects, the image of the street market will be changed as the space becomes more modernized to attract visitors. As a consequence to the redevelopment of street markets, the arrivals of visitors and the visitor experience may also change. This paper examines the role of street market as an urban cultural space for the city. Through a case study on Ferringhi Night Market, Penang, the researchers conducted a survey among the locals and tourists, semi-structured interviews among the vendors and field observation to analyse the nature of Ferringhi Night Market as a street market and how visitors and vendors experience and perceive it. The study found that Ferringhi Night Market plays heterogeneous roles as a commercial and cultural space. There are several factors that contribute to the visitor experience at Ferringhi Night Market in terms of the elements, the spaces, the surrounding site, atmosphere, local activities, products and the presence of local people. To further improve the vibrancy of Ferringhi Night Market, this study suggests that the physical setting needs to support more social activities and cultural activities.